The phoenix and the carpet - Nesbit, E. (Edith), 1858-1924; New Editions ([Hellinikon, Greece] : New Editions, 2000)
fter they discover a mysterious phoenix egg wrapped in a magic wish carpet, Robert, Anthea, Cyril, and Jane embark on a series of adventures in which anything is possible
Level 1
Keywords: Phoenix (Mythical bird) -- Juvenile fiction; Fantastic fiction; England -- Juvenile fiction; Brothers and sisters -- Juvenile fiction